Effect of M-CSF on the expression of endothelial progenitor cell markers in blood mononuclear cell culture in coronary heart disease - S. P. Chumakova; O. I. Urazova; V. M. Shipulin; M. V. Gladkovskaya; S. L. Andreev; K. V. Nevskaya; A. P. Zima; E. L. Nikulina (Бюллетень сибирской медицины, 2024)
Aim. To evaluate the nature of changes in the expression of markers of endothelial progenitor cells (VEGFR2, CD34, CD14) and endothelial cells (CD146) in association with the expression of the leukocyte common antigen CD45 in the culture of blood mononuclear cells in the presence of M-CSF in patients with coronary heart disease (CHD) and healthy donors.Materials and methods. The study included 12 patients with CHD with class III–V angina pectoris and 10 healthy donors, from whom 30 ml of venous blood was taken on an empty stomach in the morning and stabilized with heparin. Blood mononuclear cells were isolated by Ficoll density gradient centrifugation (1.077 g / cm3) and subject to immunomagnetic separation using CD14-MicroBeads and CD34-MicroBead Kit (Miltenyi Biotec B.V. & Co. KG, Germany). The resulting CD14+ and CD34+ culture of mononuclear cells was incubated for 6 days in a complete nutrient medium with and without M-CSF 50 ng / ml (Cloud-Clone Corp., USA) with complete replacement of the medium and repeated application of M-CSF on day 3. After 6 days, the proportions of CD45+, CD14+, CD34+, VEGFR2+, and CD146+ cells in the culture were assessed by flow cytometry using CD14-FITC, CD34-PE, VEGFR2-Alexa Fluor 647; CD45-FITC and CD146-PerCP antibodies (BD Biosciences, USA).Results. It was shown that in healthy donors, the proportion of CD146+ cells in the co-culture of blood mononuclear cells with M-CSF exceeded their number in the sample without it, with comparable expression rates of CD45, CD14, and VEGFR2 markers between the control and stimulated cultures. In CHD patients, the number of CD146+ and VEGFR2+ cells did not change when M-CSF was added to the mononuclear cell culture; however, the proportion of CD14+ cells increased and the proportion of CD45+ cells decreased compared to the control sample. The number of CD34+ cells was comparable both between control and stimulated samples, and between the groups of examined individuals. At the same time, in patients with CHD, an increased proportion of VEGFR2+ cells was found in the control and stimulated samples compared to healthy individuals, while an increased proportion of CD14+ cells was detected only in the stimulated culture.Conclusion. The development of CHD disrupts the response of blood mononuclear cells to the effect of M-CSF, increasing the number of CD14+ and reducing the proportion of CD45+ cells in the culture in the absence of stimulating effects on the expression of endothelial cell marker CD146. At the same time, M-CSF does not affect the expression of CD34 and VEGFR2 in endothelial progenitor cells both in patients with CHD and in healthy individuals.